History of Ukrainian Antarctic Research - V. P. Rybachuk (Ukrainian Antarctic Journal, 2010)
A brief overview of Ukrainian scientific works investigating the history of antarctic research is presented, and a scheme of periodization of the history proposed. We analyzed how the history of Ukrainian efforts in Antarctica is reflected in the encyclopedias and educationalpublications in recent years. The rational for further development of historically focused research as part of the National Antarctic research program is offered.